2005
DOI: 10.1021/jp046807l
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bond Dynamics in the Air−Water Interface

Abstract: Hydrogen-bond (H-bond) dynamics in the air-water interface is studied by molecular dynamics simulations. The analysis reveals that the dynamics of breaking and forming hydrogen bonds in the air-water interface is faster than that in bulk water for the polarizable water models. This is in contrast to the results found on a protein surface. We show that the difference stems from more rapid translational diffusion in the interface. When the effect of pair diffusion is eliminated, the hydrogen-bond dynamics in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
132
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(155 citation statements)
references
References 43 publications
21
132
2
Order By: Relevance
“…͗ e ͑z͒͘ shows nine oscillations in the bulklike liquid region, with variations in the peaks value of Ϸ0.08. These peaks reflect the mean molecular positions and likely give rise to a mobility dependence with the position in the slab, in agreement with a previous report of low diffusion coefficients found in the bulk water compared to the values found at the interface, reported by Liu et al 13 If we consider that the peaks extend across Ϸ29 Å, each peak has an average width of Ϸ3.2 Å, which corresponds to the approximate molecular diameter of water, which has been estimated from adsorption studies of water molecules in micropores. 28 To obtain information about the orientation of the permanent and induced dipoles, we calculate the angle between the dipole direction and the parallel to the interface.…”
Section: A Density and Molecular Orientationsupporting
confidence: 92%
See 2 more Smart Citations
“…͗ e ͑z͒͘ shows nine oscillations in the bulklike liquid region, with variations in the peaks value of Ϸ0.08. These peaks reflect the mean molecular positions and likely give rise to a mobility dependence with the position in the slab, in agreement with a previous report of low diffusion coefficients found in the bulk water compared to the values found at the interface, reported by Liu et al 13 If we consider that the peaks extend across Ϸ29 Å, each peak has an average width of Ϸ3.2 Å, which corresponds to the approximate molecular diameter of water, which has been estimated from adsorption studies of water molecules in micropores. 28 To obtain information about the orientation of the permanent and induced dipoles, we calculate the angle between the dipole direction and the parallel to the interface.…”
Section: A Density and Molecular Orientationsupporting
confidence: 92%
“…A previous work with a polarizable model of water found that the relaxation times for water at the bulk and at the interface are 4.93 and 4.07 ps, respectively. 13 To equilibrate, the system was slowly heated, starting from a configuration at 0 K, in order to avoid translation of the "slab" of water through the simulation cell. An illustrative snapshot of the system is shown in Fig.…”
Section: ͑6͒mentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusion within the surface is increased for some molecules (in the surface) but decreased for others and depends on the number of hydrogen bonds and size of the water clusters (Liu et al 2005). The refractive index of the surface of water at 22°C has been shown to be higher than that of the bulk and opposite in behavior to other normal and hydrogen-bonding liquids, ethanol for example (Greef and Frey, 2008).…”
Section: Surface Tension and Related Thermodynamicsmentioning
confidence: 99%
“…Berne and coworkers examined the hydrogen bond dynamics at the water liquid/vapor interface. 252 They found faster hydrogen bond dynamics at the interface than in bulk water for the polarizable water models, but slower dynamics if non-polarizable models are used. Even with the polarizable models, however, the shorter lifetime at the interface was attributed to more rapid translational diffusion at the interface rather than to faster kinetics of hydrogen bond formation.…”
mentioning
confidence: 97%